Mastering Simulation : a handbook for success - Palaganas, Janice C.; Ulrich, Beth Tamplet; Mancini, Mary E.; Sigma Theta Tau International (Indianapolis, IN : Sigma Theta Tau International, 2020)
"Simulation can be a valuable tool in academic or clinical settings, but technology changes quickly, and faculty, students, and clinicians need to know how to respond. Understanding simulation scenarios and environments is essential when designing and implementing effective programs for interdisciplinary learners. In this fully revised second edition of Mastering Simulation, nationally known experts Janice Palaganas, Beth Ulrich, and Beth Mancini guide students and practitioners in developing clinical competencies and provide a solid foundation for improving patient outcomes"--
Includes bibliographical references and index.
Keywords: Simulation Training; Patient Simulation; Competency-Based Education -- methods; Evidence-Based Practice